2008
DOI: 10.1163/22134379-90003664
|View full text |Cite
|
Sign up to set email alerts
|

The megalithic complex of highland Jambi: An archaeological perspective

Abstract: The highlands of Sumatra remain one of the most neglected regions of insular Southeast Asia in terms of history and archaeology. No comprehensive research program incorporating both a survey and excavations within a defined geographical or environmental zone has been carried out there since Van der Hoop (1932) conducted his study of the megaliths on the Pasemah plateau in the 1930s. Meanwhile, Van der Hoop’s investigations and several other archaeological research activities at places such as northwest Lampun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 1 publication
1
11
0
9
Order By: Relevance
“…These sites have a documented chronological range between the seventh and sixteenth centuries AD (Table 8.5), and evidently represent a local tradition that continued into the eleventh century when megaliths started to become a prominent feature within the local settlements (Bonatz et al 2006). …”
Section: Terra Australis 45mentioning
confidence: 99%
“…These sites have a documented chronological range between the seventh and sixteenth centuries AD (Table 8.5), and evidently represent a local tradition that continued into the eleventh century when megaliths started to become a prominent feature within the local settlements (Bonatz et al 2006). …”
Section: Terra Australis 45mentioning
confidence: 99%
“…Its existence has been known since 1873, and its translation and context was last discussed by Caldwell and Hazlewood [111] (Figure 9). More recent work has been conducted by Bonatz et al [112], whose work in Jambi Province has uncovered some 20 megaliths, often carved with decorative motifs. Most significantly, Simanjuntak [113] reported the first discovery of painted rock art in Sumatra, at the site of Gua Harimau.…”
Section: Indonesiamentioning
confidence: 99%
“…Bonatz et al (2006) argued that the people have inhabited the region since about eleventh to thirteenth centuries AD. Campbell's expedition in 1804 confirmed that the population in the region was extremely dense compared to the surrounding areas (Marsden 1811).…”
Section: Ethnobotanical Data Collectionmentioning
confidence: 99%
“…They have occupied this region for many generations before the park was established in 1999 (Bonatz et al 2006), and to some degree, they still practice and maintain their traditional life-style. This includes the ways in which they use and manage natural resources and their reliance on plants for resolving health problems.…”
Section: Introductionmentioning
confidence: 99%